Pharmacological Nature of the Purinergic P2Y Receptor Subtypes That Participate in the Blood Pressure Changes Produced by ADPβS in Rats - Roberto C. Silva-Velasco; Belinda Villanueva-Castillo; Kristian A. Haanes; Antoinette MaassenVanDenBrink; Carlos M. Villalón (MDPI AG, 2023)
Purine nucleosides (adenosine) and nucleotides such as adenosine mono/di/triphosphate (AMP/ADP/ATP) may produce complex cardiovascular responses. For example, adenosine-5'-(β-thio)-diphosphate (ADPβS; a stable synthetic analogue of ADP) can induce vasodilatation/vasodepressor responses by endothelium-dependent and independent mechanisms involving purinergic P2Y receptors; however, the specific subtypes participating in these responses remain unknown. Therefore, this study investigated the receptor subtypes mediating the blood pressure changes induced by intravenous bolus of ADPβS in male Wistar rats in the absence and presence of central mechanisms with the antagonists MRS2500 (P2Y1), PSB0739 (P2Y12), and MRS2211 (P2Y13). For this purpose, 120 rats were divided into 60 anaesthetised rats and 60 pithed rats, and further subdivided into four groups (n = 30 each), namely: (a) anaesthetised rats, (b) anaesthetised rats with bilateral vagotomy, (c) pithed rats, and (d) pithed rats continuously infused (intravenously) with methoxamine (an α1-adrenergic agonist that restores systemic vascular tone). We observed, in all four groups, that the immediate decreases in diastolic blood pressure produced by ADPβS were exclusively mediated by peripheral activation of P2Y1 receptors. Nevertheless, the subsequent increases in systolic blood pressure elicited by ADPβS in pithed rats infused with methoxamine probably involved peripheral activation of P2Y1, P2Y12, and P2Y13 receptors.